Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Dinas Pekerjaan Umum Bina Marga dan Tata Ruang Provinsi Sumatera Selatan - Deviyana Deviyana; Diah Isnaini Asiati; Fadhil Yamaly (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to determine the effect of work discipline and work environment on employee performance with work motivation as an intervening variable at the Department of Public Works, Highways and Spatial Planning, South Sumatra Province. This type of research is Associative. The sample in this study were employees of the Public Works Department of Highways and Spatial Planning of South Sumatra Province, amounting to 148 people who were selected by cluster sampling. The data used in this study are primary data with questionnaire data collection methods. The data analysis technique used is Structural Modeling Equation (SEM). The results of this study indicate that: (1) work discipline has a positive and significant effect on employee work motivation, (2) discipline has a positive and significant effect on employee performance, (3) work environment has no significant effect on employee work motivation, (4) work environment no significant effect on employee performance, (5) work motivation has no significant effect on employee performance, (6) work discipline has no significant effect on employee performance with work motivation as an intervening variable at the Public Works Department of Highways and Spatial Planning of South Sumatra Province. (7) The work environment has no significant effect on employee performance with work motivation as an intervening variable at the Department of Public Works, Highways and Spatial Planning of South Sumatra Province.